Correlation of Sleep Quality and Anxiety with Pain Intensity in Primary Headache Patients (Medico Legal Update, 2020)
Background: Headache is the most common diagnosis that is referred to a neurologist. Chronic headachesare one of the biggest challenges that are rarely handled and treated well. Therefore, the clinician shouldlook for the cause of headache in order for the patient’s complaints can be handled and not being chronic.One of the causes or risk factors for headache is sleep disturbance and anxiety.Objective: To analyze the correlationbetween sleep quality and anxiety with the intensity of pain in primaryheadache patients.Materials and Method: This is a case-control study. We obtained 52 subjects through consecutie admissionsampling. The subjects were examined for their pain intensity using Numeric Pain Rating Scale (NPRS).Sleep quality examination were performed using Pittsburgh Sleep Quality Index (PSQI) and for anxiety weused Hamilton Anxiety Rating Scale (HARS). The data were analyzed using chi-square test and paired t-test.Result: Subjects with mild NPRS (